STUDY ON CHEMICAL CHARACTERISTICS OF COAL AND BIOMASS BLEND AND THE TENDENCY OF ITS ASH DEPOSITION - Datin Fatia Umar; Taty Rohayati (Puslitbang tekMIRA, 2021)
A coal and biomasses of empty fruit bunch (EFB), mesocarp fiber (MF) and palm kernel shell (PKS) were characterized in terms of its proximate, ultimate, calorific value and ash chemical composition. Ash fusion temperature (AFT) was carried out on coal and biomass blends with a composition in weight % of 95-5; 90-10 and 85-15. The coal used in this research has high calorific value of 6,106 cal/g. Results indicate that based on the AFT, the coal-biomass blends at some composition shows a medium tendency to ash deposition. While based on the chemical composition, generally the coal-biomass blends have a low tendency to slagging but have a high tendency to fouling. Coal-biomass blend at the coal composition of 85 wt% and PKS of 15 wt% (85-15) is recommended to be applied. The less the coal is used, the less the CO2 emission, so it is expected to reduce the GHG significantly.